Self‐Assessment of Disability in Parkinson's Disease: The MDS‐UPDRS Part II Versus Clinician‐Based Ratings. Issue 4 (5th January 2017) - Rodríguez‐Blázquez, Carmen; Alvarez, Mario; Arakaki, Tomoko; Campos Arillo, Víctor; Chaná, Pedro; Fernández, William; Garretto, Nélida; Martínez‐Castrillo, Juan Carlos; Rodríguez‐Violante, Mayela; Serrano‐Dueñas, Marcos; Ballesteros, Diego; Rojo‐Abuin, Jose Manuel; et al.
Abstract: Background: Parkinson's disease (PD) is characterized by motor and nonmotor symptoms that progress with time, causing disability. The performance of a disease‐specific, self‐applied tool for assessing disability, the MDS‐UPDRS Part II, is tested against generic and rater‐based rating scales. Methods: An international, cross‐sectional, observational study was performed. Patients were assessed with the Hoehn and Yahr (HY) and five disability measures: MDS‐UPDRS Part II, Schwab and England Scale (S&E), Clinical Impression of Severity Index‐PD (CISI‐PD) Disability item, Barthel Index (BI), and Rapid Assessment of Disability Scale (RADS). Data analysis included correlation coefficients, Mann‐Whitney and Kruskal‐Wallis tests, and intraclass‐correlation coefficient for concordance. Results: The sample was composed of 451 patients, 55.2% men, with a mean age of 65.06 years (SD = 10.71). Disability rating scales correlated from |0.75| (CISI‐PD Disability with BI) to 0.87 (MDS‐UPDRS Part II with RADS). In general, MDS‐UPDRS Part II showed high correlation coefficients with clinical variables and satisfactory concordance with the rest of disability measures, with ICC ranging from 0.83 (with BI) to 0.93 (with RADS). All disability rating scales showed statistical significant differences in the sample grouped by sex, age, disease duration, and severity level. Conclusions: The MDS‐UPDRS Part II showed an appropriate performance to assess disability in PD, even better than some rater‐based, generic or specific, scales applied in this study.